THE ROLE OF COLLABORATIVE LEARNING STRATEGIES IN DEVELOPING SPEAKING SKILLS IN FOREIGN LANGUAGE STUDENTS - Saitmuratov Fariddun Farxod o’g’li; Tagayeva Madina Ilxomovna; Tolibova Sabina Bakhtiyorovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Modern usage is one of the most important aspects of developing students’ oral communication skills in language education. Many EFL (English as a Foreign Language) students face difficulties in communicating fluently in English. One of the main tools for this is effective communicative creativity in the classroom. This article analyzes the importance of collaborative learning strategies in language teaching in developing speaking skills. The article states that collaborative learning is an effective pedagogical tool for developing students’ communicative competence, helping them in the classroom and increasing their confidence in maintaining their language skills.